Impactos de investimentos em tecnologia da informação na eficiência e produtividade de países da OCDE - Araújo, Francisco Kaique Feitosa (2024)
This work analyzes the impacts of investments in information technology (IT) on the technical efficiency and productivity of countries in the Organization for Economic Cooperation and Development (OECD). The objective is to verify whether the discussion about Solow's Paradox (1987) is still valid. In this regard, a panel sample of 29 countries from 2000 to 2019 is considered. A stochastic production function is also estimated, which allows obtaining the Malmquist total factor productivity (TFP) index, which can be decomposed into technological change and efficiency change. The estimated results provide evidence that higher investments in IT positively affect technical efficiency. The TFP results show a considerable increase in productivity during the analyzed period, rejecting the hypothesis of Solow's productivity paradox.